Penghambatan Pertumbuhan Populasi Mikroba Bentuk Filamen dengan Sistem Pengolahan Limbah Anaerobik-Aerobik - I Made Sudiana (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
Bulking sludge is a common phenomenon in wastewater treatment plant (WWTP), of which due to excessive growth of filamentous bacteria. Quantity and intensity of organic substrate loading, mode of reactor operation namely aerobic, frequency of anaerobic-aerobic phase determines species and population of filamentous bacteria. Poor organic substrate input and sludge only exposed with aerobic phase appeared to stimulate growth of filamentous bacteria  021 N and 041 N types, Sphaerotilus natans, Microthrix parvicella, Nostocoida limicola, Thiothrix sp. Nocardia group, Flexibacter sp., Beggiota sp. and Haliscomenobacter hydrossis. Increasing of organic loading and sludge exposed with frequent anaerobic-aerobic phase effectively  suppressed excessive growth of Type 021 N, 041 N and Microthrix parvicella. Thus result is better in sludge sedimentation indicated by a decline sludge volume index (SVI).